2022
DOI: 10.4103/aja2021124
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Mycoplasma species on human and canine semen quality: a review

Abstract: Mycoplasma species (spp.) are bacteria that are difficult to detect. Currently, the polymerase chain reaction (PCR) is considered the most effective diagnostic tool to detect these microorganisms in both human and veterinary medicine. There are 13 known species of human Mycoplasma and 15 species of canine Mycoplasma . Owing to the difficulties in identifying the individual species of Mycoplasma , there is a lack of information rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 84 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…At the same time, they found that 20% of culture-positive samples were negative by PCR, which is currently considered the most effective method, especially since it is more sensitive than culture. However, it should be noted that PCR does not prove whether bacteria are alive or not [9,43], except when using viability PCR [44]. It is still unclear which factors have a direct influence on susceptibility to mycoplasma infections.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, they found that 20% of culture-positive samples were negative by PCR, which is currently considered the most effective method, especially since it is more sensitive than culture. However, it should be noted that PCR does not prove whether bacteria are alive or not [9,43], except when using viability PCR [44]. It is still unclear which factors have a direct influence on susceptibility to mycoplasma infections.…”
Section: Discussionmentioning
confidence: 99%
“…DNA isolation was performed using the Swab-Extract DNA Purification Kit (Eurx, Gda ńsk, Poland), following the manufacturer's guidelines. PCR reactions were performed using recently published primers specific to various Mycoplasma species [21], along with Taq PCR Master Mix (2x) (Eurx, Gda ńsk, Poland). Protocols for PCR were adapted from standard procedures described previously [22,23].…”
Section: Pcr Analysesmentioning
confidence: 99%
“…), M. hominis , M. genitalium , M. fermentans , M. spermatophilum , Ureaplasma urealyticum , Ureaplasma parvum , and some other species, have been found on the mucosal surfaces of the urogenital tracts. 1 They are commonly referred to as “urogenital Mycoplasmas ”. In men, they colonize the urethra, semen, and foreskin, and in women, the vagina and rarely the cervical canal.…”
Section: Introductionmentioning
confidence: 99%
“…In men, they colonize the urethra, semen, and foreskin, and in women, the vagina and rarely the cervical canal. 1 2 Their main route of transmission is sexual. Therefore, young people with high sexual activity and frequent partner changes, as well as persons involved in group sex and homosexuals, are more often colonized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation